Peranan Red Mud dan Pupuk Kandang Kambing Terhadap Ketersediaan Hara N, P, K Serta Pertumbuhan Tanaman Jagung pada Tanah Gambut - Tanti, Dwi; Suswati, Denah; Romiyanto, Romiyanto (Soil Science Department, Faculty of Agriculture, Tanjungpura University, 2026)
The use of peat soil as a growing medium for corn plants faces various problems regarding soil fertility and low productivity. One of the materials that can improve fertility is red mud, which can increase the pH of peat soil, and goat manure as a soil fertility improver. This study aims to determine the effect of red mud and goat manure on increasing the availability of N, P, and K nutrients in peat soil. The study was conducted at the experimental field of the Faculty of Agriculture, Tanjungpura University, and soil sample analysis was carried out at the Chemistry and Soil Fertility Laboratory of the Faculty of Agriculture, Tanjungpura University. The research design used in this study was a completely randomized design (CRD) factorial pattern and Duncan's test with a 5% confidence level, consisting of 9 treatments and 3 replicates, resulting in 27 polybags (plants). The red mud treatment doses were: M0 (0 g/polybag), M1: 100 g/polybag (4 tons/ha), M2: 200 g/polybag (8 tons/ha). Goat manure treatment doses: K0 (0 g/polybag), K1: 1500 g/polybag (60 tons/ha), K2: 3000 [A3.1]g/polybag (120 tons/ha). The parameters observed were Soil Reaction (Soil Acidity), Soil Organic Carbon, Total Soil Nitrogen (N), Available Phosphorus (P), Exchangeable Potassium (K), Plant Height, and Corn Stem Diameter. Based on the research results, it can be concluded that the M2K2 treatment with 200 g/polybag (8 tons/ha) of red mud and kambi manure.